Motor recovery after acute ischaemic stroke: a metabolic study. Issue 11 (November 1992) - Di Piero, V; Chollet, F M; MacCarthy, P; Lenzi, G L; Frackowiak, R S
Abstract : The metabolic changes occurring after ischaemic stroke were measured to investigate the functional anatomy of clinical motor recovery. Positron emission tomography (PET) and the steady-state 15O technique was used to compare resting relative metabolic distributions at the onset of functional deficit with those following recovery. Ten patients were studied with repeat scans. Motor recovery was associated in some patients with an increase of relative oxygen metabolism in anatomical structures normally involved in motor function in the affected hemisphere, particularly in the cortical motor areas. In those patients without such metabolic changes in the cortex of the diseased hemisphere, relative increases in cortical metabolism in the contralateral hemisphere were associated with better motor recovery than in patients with no relative cortical metabolic increase in either hemisphere. There was no correlation between the degree of improvement in motor function and the severity of motor deficit at onset, the size and site of the lesion and the metabolic changes in the infarcted zone. No particular pattern of global metabolic changes was observed after recovery. Thus different relative patterns of metabolic recovery were seen in patients with different lesions and evidence was found for the participation of contralateral structures in the recovery process in some patients.